Quaestiones de esse intelligibili - Petrus Thomae, approximately 1280-approximately 1340 (Ancient and medieval philosophy., 2015)
First critical edition of Petrus Thomae's theory of non-causal dependence. This work of Scotist metaphysics is an investigation into the ultimate constitution of things. In the course of this treatise, Petrus Thomae examines whether the essences of things ultimately depend on being thought of by God for their very intelligibility or whether they have it of themselves. Defending in detail the second option, Peter argues that creatures exist independently of the divine intellect in the divine essence. They enjoy real, eternal being in the divine essence and objective being in the divine mind. Aware that these views conflicted with his belief in the Christian doctrine of creation, Peter laboured to alleviate the conflict with a theory of non-causal dependence, according to which even if God did not cause creatures to be in the divine essence, nevertheless they are necessary correlatives of the divine essence.